Tackling the challenge of social connection through dining-focused platforms - technical framework, logic, and implementation from requirements to execution - Wang, Wanchen (2025)
When adapting to new environments, newcomers often struggle to expand their social circles and integrate into local life, lacking effective platform support. This thesis revolves around the development and implementation of Nibble, an innovative social dining application that integrates trusted dining recommendations, flexible dining organization, personalized user profiles and posting content. Nibble, based on the Bubble No-Code platform, simplifies technical implementation and ensures rapid response to user requirements. Nibble blends dining with social activities, offering newcomers opportunities to integrate into urban life and fostering cultural integration.